Proses Perubahan Diri Seorang Teroris menjadi Aktivis Perdamaian - Muhammad Syafiq (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2021)
This qualitative study was aimed at exploring the experience of a former member of a terrorist organization in Indonesia who have left his terrorist group and abandoned the extremist ideology. A life history method which focuses on the process of self-change and life transition of the former member of the terrorist group was employed A participant whose age is 40 years old and was a former active member of Jamaah Islamiyah (JI), a terrorist group, was recruited. He was captured in 2014 and served a sentence in prison for almost 4 years. He has been involved in counter-terrorism campaign organized by a non-government organization (NGO) since his release from prison until recently. Interviews were conducted to collect data which were then analyzed using a narrative analysis. Some written documents in the forms of articles and a published book produced by the participant as well as online news covering the participant’ stories were also examined. The findings inform how he became involved in the terrorist networks. The need for self-significance and adventurous experience seems to be the main drivers. After his capture, and during his imprisonment, he contemplated his participation in the terrorist networks. His meetings with religious experts and academicians facilitated by prison officers, and his awareness of burden he had inflicted on his family because of his terrorism case had opened his mind. He experienced a turning life moment which made him keeping distance from other terrorist inmates with the risk of receiving negative view from them. After his release, he found passion in writing and eventually reached a NGO and joined it as a credible voice in the campaigns of counter violent extremism through writing and public speaking.